Water for development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Water supplies for rural communities by Colin and Mog Ball 1991 56pp ISBN 1-85339-112-3 pbk UKL5.95